REVEALING THE REALITIES IN QATAR AIRWAYS’ MARKETING COMMUNICATION: A CDA - Mentari Putri Pramanenda Sinaga (Journal of Language, Literature and Teaching, 2022)
A new product or service must be introduced publicly to attract the new users to buy. This is called a marketing communication. A YouTube channel can be one of the effective tools to maximize users’ engagement and attention. Qatar Airways has promoted a new on-board Boeing 787 Dreamliner on their Youtube Channel. Through their prestigious service and facilities, and also convincing statements, the video persuades the video viewers. The study investigates how the Qatar Airways’ marketing communication marginalize economy passengers and manipulate potential users. The critical discourse analysis is employed to examine the linguistics aspects and visual images. The three-dimensional model by Fairclough (1995) frames the analysis through the text analysis, discursive practice, and social practice. The data were taken from the written video caption, the transcription of the video, and also 28 scenes of the video’s screen capture. The findings reveal the realities of how the video forms the identity, specifies the facilities, and distinguishes service for each class of passengers; first class, business, premium economy, and economy class. They manifest discrimination which is hidden by the claim of 5-star touch and glamorous ambient.Keywords: Critical Discourse Analysis, Marketing Communications, Three-dimensional Model